Effectiveness of Automatic Section Speed Control System Operating on National Roads in Poland - Ziolkowski, Robert (Promet - Traffic&Transportation, 2019)
Driving speed remains within the most important factors in road safety, and speed not only affects the severity of a crash but is also related to the risk of being involved in a crash. Inappropriate speed is responsible for more than a third of all fatal accidents occurring on roads. In Poland the problem of speeding drivers is widely present. Hence, effective speed management and enforcement of speed limits on existing roads plays an important role. Possible solutions for rural roads are very limited and are focused mainly on administrative speed limitations and speed cameras enforcement. However, due to their limited effectiveness new solutions are still being sought. High expectations are associated with the automatic section speed control system that has recently been introduced in Poland. The aim of this paper is to examine the efficiency of the automatic section speed control system on the basis of speed surveys collected on chosen national roads where the system for sectional speed control was first implemented. Conducted comparisons and statistical analyses included driver’s average speed, speed percentiles, the number of speeding drivers as well as speed heterogeneity. To evaluate the efficacy of the sectional speed system, speed measurements were also conducted on fourteen, similar in geometry and functional characteristics, reference national roads located in Podlaskie voivodship in Poland without any specific speed enforcement.